2020
DOI: 10.1177/0017896920959690
|View full text |Cite
|
Sign up to set email alerts
|

College students’ preferences for information on self-initiated sexually transmitted infection testing

Abstract: Objective: The purpose of this study was to identify preferences for content, method of delivery and frequency of information to encourage self-initiated sexually transmitted infection (STI) testing. Design: Qualitative study involving individual in-depth interviews with 35 college students aged 18–24 years. Setting: A university in Central Pennsylvania, USA. Method: Data were collected using a demographic and sexual history questionnaire, Sexually Transmitted Disease Knowledge Questionnaire and a semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…As such, introducing DTC methods at college orientations or through RAs in college residence halls offers an opportunity to improve STI testing among young adults. A study of information about DTC methods in college settings found that email was a preferred communication channel because of the privacy it allowed 19 . In addition, women who were screened in the past year ranked college resources as more important than those who had not, which may translate to higher trust in the college healthcare system among these women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, introducing DTC methods at college orientations or through RAs in college residence halls offers an opportunity to improve STI testing among young adults. A study of information about DTC methods in college settings found that email was a preferred communication channel because of the privacy it allowed 19 . In addition, women who were screened in the past year ranked college resources as more important than those who had not, which may translate to higher trust in the college healthcare system among these women.…”
Section: Resultsmentioning
confidence: 99%
“…A study of information about DTC methods in college settings found that email was a preferred communication channel because of the privacy it allowed. 19 In addition, women who were screened in the past year ranked college resources as more important than those who had not, which may translate to higher trust in the college healthcare system among these women. To expand this trust, college healthcare providers and clinics may consider incorporating outreach into their programming to earn the same trust from the larger population of women who may benefit from STI screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological well-being education is an important content of quality education in universities, and it is an objective need for university students to grow into talents. Strengthening psychological well-being education in universities has important practical significance [1]. As an important part of college education and students' ideological and political work, it is an important way and means to implement quality education, promote the all-round growth of university students and improve the quality of personnel training [2].…”
Section: Introductionmentioning
confidence: 99%